RISK FACTORS FOR STROKE: A PROSPECTIVE HOSPITAL BASED STUDY - Rathore, Javed Akhter; Kango, Zulfiqar Ali; Nazir, Munazza; Mehraj, Adnan (Journal of Ayub Medical College Abbottabad, 2013)
Background: The stroke is third leading cause of death in world and most patients die with an acute event in stroke. Various clinical variables have been investigated as risks factors of stroke. The study was aimed to identify these risks factors for stroke. Methods: This prospective study included 205 consecutive patients of stroke admitted in Combined Military Hospital/Sheik Khalifa Bin Zyad Hospital Muzaffarabad Azad Kashmir. The risk factors of stroke were investigated. Examination included clinical, neurological evaluation, laboratory tests, and brain CT. The follow-up at 14 days were done for all patients. Patients included were with acute first ever stroke onset of 48 hours of hospital admission. All patients completed a structured questionnaire and a physical examination and most provided blood for relevant investigations. Results: Two hundred and five cases stroke sub-types were (n=156, 76%, with ischemic stroke (CI); n=49, 24%, with intra-cerebral hemorrhagic stroke (ICH). The significant risk factors for all stroke were: Hypertension (p=0.003), diabetes (p=<0.001), Hypercholesterolemia (p=0.686); atrial fibrillation (p=0.445), cardiac diseases (p=0.938), smoking (p=0.926) for brain infarction and hypertension (p=0.002), diabetes (p=<0.001), Hypercholesterolemia (p=0.018); atrial fibrillation (p=0.449), cardiac diseases (p=0.749), smoking (p=0.829) for hemorrhagic stroke. Age significance (CI; p=0.247 vs. ICH; p=0.013) and age category significance were (CI; p=<0.001 vs. ICH; p=0.871) for subtype of stroke. High mRS (p<0.001) low GCS score (p<0.001) on admission were associated with worst outcome for both stroke subtype. These risk factors were all significant for CI as well as ICH. Conclusions: This study signifies the association of risks factors with acute stroke. Targeted interventions that reduce these risk factors could substantially reduce the burden of stroke Keywords: Acute stroke; Risk factors, Outcome